Euthyroidectomy under local versus general anesthesia in health camp settings in Uganda: a protocol for randomized prospective equivalence single-blind controlled trial - Kabuye Umaru; Fualal Jane Obudu; Lule Herman (United Kingdom, 2025)
Background: Endemic goiter is highly prevalent in Uganda at 60.2%, contributing to the high surgical burden. While compelling evidence suggest that in selected cases, thyroidectomy under local anesthesia (LA) is associated with fewer post-operative complications, low costs, and short hospital stays, local anesthesia is not considered a priority technique for thyroidectomy in resource-constrained settings such as Uganda, despite having fewer general anesthesia (GA) and critical care providers. The objective of this trial is to compare euthyroidectomy under local versus general anesthesia among patients with grade 1-2 uncomplicated euthyroid goiter in Uganda.
Methods: This prospective equivalence randomized, single-blind controlled trial protocol will be conducted among eligible participants with grade 1-2 uncomplicated euthyroid goiters. The recruitment processes will start in October 2022 and end in April 2023. Consenting participants with an indication for thyroidectomy will be randomized into two arms of 29 participants in each arm during the Bulamu Health Care Organization surgical camps in Uganda.
Discussion: The primary outcome of this trial protocol is to compare the early post-operative complications of euthyroidectomy done under LA versus GA. The outcome variables include post-operative pain based on visual analogue scale, nausea, vomiting, hematoma formation, and transient voice changes determined at an interval of 6, 12, and 24 h and at 30 days. In addition, we shall compare the surgical site infection rates, procedure costs, hospital stay, and patients' level of satisfaction based on a 5-point Likert scale and their willingness to undergo a similar surgery using the same anesthetic technique between the two groups. We hypothesize that euthyroidectomy under LA could potentially offer similar benefits as GA, reduce costs related to procedure, complications, and hospital stay while at the same time mitigating the unmet need for surgery attributable to shortage of general anesthesia providers and critical care facilities in low-income settings.
Trial registration: Pan African Clinical Trial Registry PACTR202208635457430. Registered on 11th August 2022. All items from the WHO trial registration data set are within the protocol. Version number and date: version 3, 15/03/2023.